Analysis of Religiosity and MSME’s Performance: the Mediating Role of Enterpreneurial Orientation - Parlyna, Ryna; Susanto, Parengki; Abror, Abror; Marsal, Arif (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2023)
This study aims to examine the impact of religiosity on MSME’s performance using a quantitative method. Primary data were collected by distributing questionnaires to the MSME’s owners and managers. Employing purposive sampling technique, a total of 300 respondents were recruited. SMART PLS SEM 3.0 approach was implemented to analyze the data. One result show that there is a positive and significant relationship between entrepreneurial orientation and MSME’s performance. Another result is that there is a positive and significant correlation between religiosity on entrepreneurial orientation, but there is a positive and insignificant correlation between religiosity on MSME’s performance. The interesting finding in this study is that entrepreneurial orientation mediates the relationship between religiosity on MSME’s performance.